The Teaching of Photosynthesis in Secondary School: A History of the Science Approach. Issue 3 (2nd July 2016) - Métioui, Abdeljalil; Matoussi, Fathi; Trudel, Louis
Abstract : In this article we present a synthesis of the research affecting pupils' conceptions of photosynthesis and plant nutrition. The main false conceptions of the pupils identiﬁed in this literature review are: that green plants ﬁnd their food in the soil; that water and mineral salts are sufﬁcient to the growth of a plant; the role of chlorophyll, where the transformation of luminous energy into chemical energy is never evoked; and air as a source of matter, which is never underlined. Secondly, we are going to see that several of these false conceptions have been developed during history. For example, the famous philosopher Aristotle (384–322 BC) thought that plants receive their food from the soil already elaborated. Several centuries later, the physician and chemist Van Helmont (1677–1644) added more precision to Aristotle's conception while claiming that plants use only water for their growth. Finally, we will see that the analysis of the false theories developed during history will permit in a context of teaching to valorize the false conceptions of the pupils. Indeed, the history of sciences could incite a teacher to valorize his pupils' false conceptions while considering them as an indication of difficulties that deserve particular pedagogical and didactic tools. The false conceptions constructed by the pupils don't have to be ignored in a teaching context because they obey particular reasoning rules, sometimes similar to those that once guided some scientific steps. This view, drawing on false conceptions developed during history, gives a dynamic and human picture of the science very distant from the one sometimes carried on by dogmatic teaching.